VENOUS THROMBOEMBOLISM IN RELATION TO OVARIAN HYPERSTIMULATION SYNDROME: AN APPROACH TO DETERMINING THE LOW-MOLECULAR-WEIGHT-HEPARIN DOSES AND ACTIVITY - I. E. Zazerskaya; N. A. Osipova; T. V. Vavilova; L. V. Barabanova; K. S. Konradi (IRBIS LLC, 2016)
Ovarian hyperstimulation syndrome (OHSS) is a relatively common complication of ovarian stimulation. The pathophysiology of OHSS is characterised by increased capillary permeability. As a consequence of this, there is a fluid shift into third-space causing hemoconcentration, it may contribute to hypercoagulable state, with increased riskof venous thromboembolism. The article presents modern data on prevention of thromboembolic complication in OHSS patients with special focus on dosage and duration of thromboprophylaxis.